2017
DOI: 10.1093/ejcts/ezx280
|View full text |Cite|
|
Sign up to set email alerts
|

No improvements in long-term outcome after coronary artery bypass grafting with arterial grafts as a second conduit: a Swedish nationwide registry study

Abstract: Patients who had arterial grafts as second conduits did not demonstrate a better outcome in any of the studied end-points. Radial artery grafts seem to be preferable to BIMA grafts as an alternative to an SVG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 17 publications
0
11
0
2
Order By: Relevance
“…Cardiovascular disease (CVD) remains the second cause of death worldwide in spite of current advances in treatment including pharmacological development, instruments for intervention, techniques for coronary artery bypass surgery (CABG), and percutaneous coronary intervention (PCI) as well as educational guidelines for prevention . This highlights the need for a safe and efficient therapeutic alternative.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular disease (CVD) remains the second cause of death worldwide in spite of current advances in treatment including pharmacological development, instruments for intervention, techniques for coronary artery bypass surgery (CABG), and percutaneous coronary intervention (PCI) as well as educational guidelines for prevention . This highlights the need for a safe and efficient therapeutic alternative.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Janiec, et al 2017 (34) & Hayward, et al 2011 & 2013 (21&22) concluded almost the same result that, Patients who received arterial grafts as second conduits did not demonstrate a better outcome in any of the studied endpoints, as reported by Janiec.…”
Section: Discussionmentioning
confidence: 62%
“…While the results of Janiec, et al 2017 (34) & Hayward, et al 2011 & 2013 (21&22) show that RA & SV have almost the same incidence rates of either PCI intervention or coronary surgery repetition. On the other hand, the results of Deb, et al 2012 (19) , Petrovic, et al 2015 (17) , Yamasaki, et al 2016 (20) & Gaudino, et al 2018 (26) showed that using RA has lower rates of the need for revascularization either by PCI or redo CABG than using SV.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Data on the use of MAG are relatively limited for both North America and Europe (Table 3). [22][23][24][25][26][27][28][29][30] In a review of The Society of Thoracic Surgeons (STS) Adult Cardiac Surgery database including 1,493,470 patients undergoing CABG between 2004 and 2015, Schwann and colleagues 22 reported a rate of MAG of 11.3%, with a significant decrease from 16% in 2004 to 9% in 2015. In another report from the STS database focused on low-risk patients most likely to benefit from MAG (age <70 years, no or mild chronic lung disease, body mass index <30 kg/m 2 , and absence of diabetes), Lapar and colleagues 31 reported a BITA use rate of 6%.…”
Section: Prevalence Of the Use Of Magmentioning
confidence: 99%